(3EOGQI GdJShjbs - (3OYGA eSYhO(B, (3VeQIs ((3YeGf(B:s (3GdeLJeY GdYQHj(B,s, 2006)
(3eaghe GdJShjb(B-(3OQGSI GdShb hJMdjdg(B-(3Sdhc GdeSJgdc(B-(3GdYfGUQ GdCSGSjI dMXI Yed LjOIs
Keywords: (3COGQI GdeHjYGJs; (3EOGQI GdCYeGds; (3GdJShjbs